Information Dissemination in Heterogeneous-Intent Networks - Das, Abhimanyu; Gollapudi, Sreenivas; Kiciman, Emre; Varol, Onur (Web Science, 2016)
Individual’s motivations for participating in social networks can vary greatly, and this heterogeneity is reﬂected in the wide-variety of behaviors and communication styles we see in large social networks. In this paper, we present a ﬁrst study of the basic properties of communication in a heterogeneous-intent network and their implications. First, through both user studies and large-scale data analyses, we validate that individual’s speciﬁc intents aﬀect their style of communication and their selection of messages. Secondly, we propose a simple structural model of information diﬀusion within a heterogeneous-intent network and present the results of experiments exploring its emergent properties, ﬁnding that it recreates aspects of empirically observed cascades that are not captured in previous models.